2021
DOI: 10.1002/lpor.202000588
|View full text |Cite
|
Sign up to set email alerts
|

Optical Vernier Effect: Recent Advances and Developments

Abstract: The optical analog of the Vernier effect applied to fiber interferometers is a recent tool to enhance the sensitivity and resolution of optical fiber sensors. This effect relies on the overlap between the signals of two interferometers with slightly detuned interference frequencies. The Vernier envelope modulation generated at the output spectrum presents magnified sensing capabilities (i.e., magnified wavelength shift) compared to that of the individual sensing interferometers that constitute the system, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(43 citation statements)
references
References 75 publications
3
40
0
Order By: Relevance
“…In this work, we studied the conditions for generating the Vernier effect and its applications in practice. Consistent with previous studies of Vernier effect [28,37], the envelope of the Vernier effect is regenerated when the OPL of the interferometer changes proportionally. However, we found that there is a regular expansion and contraction of the The temperature characteristics of the combination of the reference and the sensing FPI are tested by placing the sensors on a heating table with a temperature range from 41 • C to 45 • C. To clearly compare the interference spectra under different temperature, Figure 13c,d shows the total reflectance spectra based on Vernier effect when the temperature rises and drops.…”
Section: Experiments and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this work, we studied the conditions for generating the Vernier effect and its applications in practice. Consistent with previous studies of Vernier effect [28,37], the envelope of the Vernier effect is regenerated when the OPL of the interferometer changes proportionally. However, we found that there is a regular expansion and contraction of the The temperature characteristics of the combination of the reference and the sensing FPI are tested by placing the sensors on a heating table with a temperature range from 41 • C to 45 • C. To clearly compare the interference spectra under different temperature, Figure 13c,d shows the total reflectance spectra based on Vernier effect when the temperature rises and drops.…”
Section: Experiments and Discussionsupporting
confidence: 90%
“…In this work, we studied the conditions for generating the Vernier effect and its applications in practice. Consistent with previous studies of Vernier effect [28,37], the envelope of the Vernier effect is regenerated when the OPL of the interferometer changes proportionally. However, we found that there is a regular expansion and contraction of the envelope during the regeneration process, which means that there is a turning point in the trend of change.…”
Section: Experiments and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed mode-selection phenomenon can be understood with the Vernier effect, which is caused by the detuning (Δ)-dependent destructive interference 4 , 5 , 12 , 14 , 44 , 45 . In principle, the magnified free spectral range ( FSR enlarged ) of the Vernier envelope 46 , 47 can be expressed as a function of the FSRs of the two coupled microdisks where FSR right and FSR left are the FSRs of the two tangent microdisks. For the case of d left = 100 μm, the diameter difference between two microdisks (Δd) is as small as 80 nm to realize the designed spectral range (300 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Leveraging on the slight scale difference between the Vernier and the main ruler, the Vernier effect was initially employed in the Vernier caliper to improve the length measurement accuracy. Recently, the Vernier effect has been revealed to be a useful technique to enhance the sensing performance of optical fiber sensors, which can greatly improve the detection resolution of fiber sensors [ 6 , 7 ]. In fact, the Vernier-effect-based optical fiber sensors have demonstrated a huge potential to achieve high sensitivity and resolution, and research on optical fiber sensors based on the Vernier effect rapidly became a popular topic among researchers during the last five years.…”
Section: Introductionmentioning
confidence: 99%